Authorship Trends in Spine Publications From 2000 to 2015. Issue 17 (1st September 2018) - Haws, Brittany E.; Khechen, Benjamin; Movassaghi, Kamran; Yom, Kelly H.; Guntin, Jordan A.; Cardinal, Kaitlyn L.; Shoshana, Noah B.; Singh, Kern
Abstract : Study Design: Literature review. Objective: To examine changes in authorship characteristics for Spine publications from the year 2000 to 2015. Summary of Background Data: Scientific publications are considered an indication of academic achievement for physicians. Recently, authorship trends have been investigated; however, limited information is available on this topic within spine-specific literature. Methods: Original research articles published in Spine in the years 2000, 2005, 2010, and 2015 were evaluated. Authorship characteristics were collected for each article, including the number of authors and institutions per publication, first and last authors' sex, publication origin, and highest degree held by the first and last author. Trends over time were analyzed using numeric and visual descriptive analyses including percentages, means, standard deviations, and graphs. Results: An average of 506 articles per year was published in Spine during the years 2000, 2005, 2010, and 2015. The number of articles written by 10 or more authors increased during this time (0.9%–14.4%). There was a substantial increase in the number of multiple institutional affiliations (33.6%–68.7%) and articles originating from outside North America (47.6%–55.7%) from 2000 to 2015. The percentage of first authors with bachelor's degrees was higher in 2015 (6.6%) as compared to 2000 (1.4%), and more last authors were identified as MD/PhDs in 2015 (19.2%) than in 2000 (10.0%). Similar female representation was noted for first and last authorship for all years evaluated. Conclusion: The results of this study demonstrate increases in authors per article published in Spine from 2000 to 2015. In addition, first authors were more likely to hold bachelor's degrees over time. This may be attributed to increasing competition in spine-related fields, necessitating earlier research exposure to aid in academic achievement. Interestingly, the percentage of female authorship has not changed significantly over time, in contrast with much of the previous literature. Level of Evidence: 2